2023
DOI: 10.2478/crebss-2023-0002
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling the diverse efficacy of artificial neural networks and logistic regression: A comparative analysis in predicting financial distress

Abstract: The prediction of financial distress has emerged as a significant concern over a prolonged period spanning more than half a century. This subject has garnered considerable attention owing to the precise outcomes derived from its predictive models. The main objective of this study is to predict financial distress using two types of Artificial Neural Networks (ANN) compared to the Logistic Regression (LR), and this will be done by relying on the data of 12 Algerian companies for the period 2015-2019. The reason … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…(Sabek & saihi, 2021) used back-propagation Neural Network to predict financial distress, and concluded that this network has a high ability to classify correctly. (Sabek A. , 2023) compared two types of Artificial Neural Networks (ANNs) with Logistic Regression (LR), and concluded that some types of ANNs are better than LR in classification and others are not. (Sabek & Horak, 2023) used Gaussian Process Regression (GPR) to predict financial distress, compared its results with deep learning models, including LR, and concluded that GPR is better than LR and all other models, except for Support Vector Machine, which achieved the same classification accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…(Sabek & saihi, 2021) used back-propagation Neural Network to predict financial distress, and concluded that this network has a high ability to classify correctly. (Sabek A. , 2023) compared two types of Artificial Neural Networks (ANNs) with Logistic Regression (LR), and concluded that some types of ANNs are better than LR in classification and others are not. (Sabek & Horak, 2023) used Gaussian Process Regression (GPR) to predict financial distress, compared its results with deep learning models, including LR, and concluded that GPR is better than LR and all other models, except for Support Vector Machine, which achieved the same classification accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%